ASPECTS OF THE VOCABULARY OF KENYAN ENGLISH: AN OVERVIEW (The University of Nairobi Journal of Language and Linguistics, 2023)
From a variety of sources, this paper has gleaned a substantial amount ofinformation on specific aspects of the vocabulary of the Kenyan Englishvariety. This information provides evidence that as a second languagevariety Kenyan English has developed its vocabulary through the mainprocesses of a) borrowing from indigenous languages, b) coining its ownwords and phrases, and c) giving, to a number of international Englishwords, additional meanings that are specific to it. The loan words fromindigenous languages are no doubt more visible than the other twocomponents of Kenyan English vocabulary, but they are numerically muchless important than these two.